Evaluation of mortality of COVID-19 patients with acute kidney injury (AKI) in comparison to the non-AKI patients - Heshmatollah Shahbazian; Mina Tafazoli; Leila Sabet Nia; Ali Ghorbani; Shahla Ahmadi Halili; Fatemeh Jahangiri Mehr (Journal of Nephropathology, 2023)
Introduction: Acute kidney injury (AKI) is prevalent in the coronavirus disease-2019 (COVID-19). There are little data on the relationship between renal dysfunction and COVID-19 prognosis. Objectives: The aim of this research was to investigate the effects of AKI in COVID-19 patients hospitalized to the Golestan and Razi hospitals in Ahvaz, Iran. Patients and Methods: In this retrospective cohort study, a total of 194 COVID-19 patients were included, consisting of 79 patients with AKI and 115 patients without AKI. Primary and secondary outcomes were compared between the two groups. Results: According to the findings, mortality was significantly different between the two groups, and mortality was higher in the AKI group (P< 0.001). The mean length of hospital stay was statistically significantly higher in the AKI group (P=0.024). Moreover, there was a significant correlation between intensive care unit (ICU) admission and the study group (P<0.001). Staging of AKI group were seen as; stage I (49.37%), stage II (36.71%), and stage III (13.92%). No significant correlation was observed between outcome and the stages of AKI (P=0.496). Furthermore, 14 patients (17.72%) needed renal replacement therapy (RRT) in the AKI group. Conclusion: Although AKI is a common finding in COVID-19 patients, most patients were in stage I disease, which returned to normal after COVID-19 treatment. According to our research, COVID-19 rarely leads to serious and persistent kidney injury. However, the risk of death is increased in COVID-19 patients with AKI. Therefore, it is necessary to evaluate the renal function tests during the course of disease.